The Seed Oil of Withania somnifera W.S.-20 Variety - Pachori, Monika; Rathee, P.S.; Mishra, S.N. (Asian Journal of Chemistry, 2010)
Withania somnifera (W.S-20 variety) seeds contain 10.1 per cent oil. The GLC analysis revealed the presence of linoleic 60.08, Oleic 18.53, palmitic 20.07, stearic 0.69, myristic 0.10 and an unknown acid 0.45 per cent.